The effects of urea content on the structural, thermal and morphological properties of MgO nanopowders - Ercan, Ismail; Kaygili, Omer; Ates, Tankut; Gunduz, Bayram; Bulut, Niyazi; Koytepe, Suleyman; Ozcan, Imren (Elsevier Sci Ltd, 2018)
In the present study, we have looked into the effects of the amount of the combustion fuel of urea on the morphological, thermal and morphological properties of MgO structure. To this goal, three Magnesium Oxide (MgO) samples were synthesized by the combustion method and the as-mentioned properties were characterized by the experimental analysis techniques of X-Ray Diffraction (XRD), Differential Thermal Analysis (DTA), Thermogravimetric Analysis (TGA) and Scanning Electron Microscopy (SEM). The functional groups in the samples were also determined using Fourier Transform Infrared (FTIR) spectrometry. The crystallinity percent values for each sample were found to be about in the range of 94-96%. The crystallite sizes of the samples were computed to be in the ranges of 26-37 nm and 23-32 nm for Scherrer and Williamson-Hall methods, respectively. The increasing quantity of urea caused a gradual growth in the lattice parameter of Magnesium Oxide structure. The thermal properties and morphology were affected by the urea content.
Keywords: MgO; X -Ray diffraction (XRD); Differential thermal analysis (DTA); Thermogravimetric analysis (TGA); Combustion method